Agrarian Conflict in Air Kumbang District, Banyuasin Regency - Indah; Rylian Chandra; Najmi Muhammad Fadli (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze the dynamics of agrarian conflict between the communities of Desa Sebubus and Air Kumbang Bakti and PT. Andira Agro Tbk, as well as to examine the community's efforts to seek agrarian justice. The research adopts a qualitative approach, utilizing in-depth interviews and document studies to collect data from various stakeholders involved in the conflict. The theoretical framework includes Wiradi Gunawan's agrarian conflict theory, emphasizing structural inequalities in land ownership between large corporations and local communities, and Sajogyo's socio-economic agrarian theory, which explains agrarian conflict as a result of imbalanced social relations and the shift of land functions from social purposes to dominant economic commodities. Findings reveal significant disparities in land control, where PT. Andira Agro Tbk holds extensive core plantation land while the community struggles to access their rightful plasma land. The company's failure to comply with the obligation to provide at least 20% plasma land as mandated by Plantation Law No. 39 of 2014 highlights structural injustice as the root cause of the conflict. Furthermore, unclear regulations, weak legal protection for indigenous land rights, and criminalization of residents attempting to defend their rights exacerbate the conflict. The study comprehensively portrays the social, economic, and legal aspects underlying the conflict and describes ongoing efforts toward resolution by involved parties.